2021
DOI: 10.7554/elife.74512
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structures and conformations of protocadherin-15 and its complexes on stereocilia elucidated by cryo-electron tomography

Abstract: Mechanosensory transduction (MT), the conversion of mechanical stimuli into electrical signals, underpins hearing and balance and is carried out within hair cells in the inner ear. Hair cells harbor actin-filled stereocilia, arranged in rows of descending heights, where the tips of stereocilia are connected to their taller neighbors by a filament composed of protocadherin 15 (PCDH15) and cadherin 23 (CDH23), deemed the ‘tip link’. Tension exerted on the tip link opens an ion channel at the tip of the shorter s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…We used the base dimers anticipating that Cdh23 exists as a base dimer in hair cells via the PICA-like domain. Though such a PICA-like domain has been bioinformatically verified for Cdh23, recent cryo-electron micrographs clearly demonstrated bifurcated C-termini for Cdh23 in tip links …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used the base dimers anticipating that Cdh23 exists as a base dimer in hair cells via the PICA-like domain. Though such a PICA-like domain has been bioinformatically verified for Cdh23, recent cryo-electron micrographs clearly demonstrated bifurcated C-termini for Cdh23 in tip links …”
Section: Resultsmentioning
confidence: 99%
“…The in situ electron micrograph of stereocilia clearly depicted the thread-like arrangement of tip links. , Subsequently, myriad studies have been employed to identify the conformational and structural origin of the thread-like tip links . It was soon revealed that the constituent cadherins, Pcdh15 and Cdh23, may exist as lateral dimers and form helically shaped tip links.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The in-situ electron micrograph of stereocilia clearly depicted the thread-like arrangement of tip-links 12 , 25 . Subsequently, myriads of studies have been employed to identify the conformational and structural origin of the thread-like tip-links 26 .…”
Section: Discussionmentioning
confidence: 97%